2022
DOI: 10.2147/cia.s356910
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Health Metrics with Dementia in Rural Chinese Older Adults: A Population-Based Study

Abstract: Purpose We explore the associations of individual and composite cardiovascular health metrics with all-cause dementia, Alzheimer’s disease, and vascular dementia among rural-dwelling older adults and the potential age variations in their associations. Patients and Methods This community-based cross-sectional study included 4980 older adults (age ≥65 years; 57.23% women) from the baseline examination of MIND-China. In March–September 2018, data were collected via face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Doctors at local town hospitals use commercial electronic blood pressure monitors (Omron HEM-7127J; Omron Corporation, Kyoto, Japan) to measure the arterial blood pressure of all participants [ 11 ]. For each blood pressure measurement, the subjects were required to sit still for 5 min so that the cuff was aligned with the heart level.…”
Section: Methodsmentioning
confidence: 99%
“…Doctors at local town hospitals use commercial electronic blood pressure monitors (Omron HEM-7127J; Omron Corporation, Kyoto, Japan) to measure the arterial blood pressure of all participants [ 11 ]. For each blood pressure measurement, the subjects were required to sit still for 5 min so that the cuff was aligned with the heart level.…”
Section: Methodsmentioning
confidence: 99%
“…The associations between CVH and cognitive function have been examined before. Guided by LS7, a number of studies demonstrated favorable CVH scores in reducing the risk of cognitive impairments and dementia [22,23]. Specifically, the protective effects of LS7 were detected to correlate with better cognitive function among older US adults [24].…”
Section: Comparison and Interpretationsmentioning
confidence: 99%